(untitled) (PHARMACON, 2013)
Medicine gives lots of benefits for human being, if it used properly. Improper use of drugs cause problem with health, medication failure, even death (WHO, 2004). Antibiotic as drugs which cure infection must be used correctly. One of antibiotics most used by society is amoxicillin. The aims of this research was to find out how far the knowledge of Manado city society about antibiotic especially amoxicillin. This research was descriptive with cross sectional approach. Sampling method were quota sampling namely 150 respondens of Manado city people which divided into three groups : health student, health workers and non health workers. Based on results, Manado city society possess middle knowledge about amoxicillin antibiotics by 49,3 %. Most of respondents in health workers group possess high knowledge by 70 %, health student possess middle knowledge by 68 %, and non health workers possess middle knowledge by 52 % about amoxicillin antibiotic. Keywords: Antibiotic, Amoxicillin, knowledge